AB0920 Tumour necrosis factor inhibitors persistence in psoriatic arthritis patients. (12th June 2018) - Vieira-Sousa, E.; Eusébio, M.; Ávila-Ribeiro, P.; Khmelinskii, N.; Machado, A.R.; Martins Rocha, T.; Bernardes, M.; Santos-Faria, D.; Leite Silva, J.; Santos, H.; Miguel, C.; Carvalho, P.; et al.
Abstract : Background: Tumour necrosis factor inhibitors (TNFi) lead to a dramatic improvement in the management of psoriatic arthritis (PsA). Nevertheless, a significant proportion of patients still do not respond and/or are intolerant to TNFis, requiring treatment switch for an adequate control of disease activity. Objectives: To assess TNFis drug retention and the main reasons for TNFi discontinuation in PsA patients. Methods: This was a non-interventional study of PsA patients registered at the Rheumatic Diseases Portuguese Registry (Reuma.pt), with at least one TNFi prescription. Drug retention for a first, second and third line TNFi was assessed by Kaplan-Meier survival analysis. The reasons for discontinuation were described as frequencies. Results: 750 PsA patients were included, with a mean age of 47.6 years (±11.6); 50.3% (n=377) female. 200 patients (26.7%) treated with adalimumab, 335 (44.7%) with etanercept, 114 (12.2%) with golimumab and 101 (13.5%) with infliximab, as first line TNFi. The majority (67.6%) were receiving concomitantly conventional synthetic disease modifying anti-rheumatic drugs (62.3% MTX) and 33.9% corticosteroids. The mean duration of TNFi retention was of 48.5±40.1 months, when treated with a 1st TNFi, decreasing to 35.5±33 months for the 2nd TNFi, and to 22.7±22.9 months for the 3rd TNFi (figure 1). After being treated with a 1st TNFi, the majority of discontinuers (35, 8% of the total population), withdraw due to lack or loss of effectiveness (53.5%) and due to adverse events (24.4%). The rates of discontinuation for the 2nd and 3rd TNFi were of 39% and 54%, respectively. Lack or loss of effectiveness and adverse events were maintained the two main reasons of withdrawal for the 2nd (62.3%; 21.6%) and 3rd TNFi (63%; 22.2%). Conclusions: PsA patients registered at Reuma.pt treated with a 1st TNFi had an overall drug retention of 49 months. We observed a decrease in the average retention of TNFi therapy of 13.0 months in PsA patients who switched to a 2nd TNFi or a 3rd TNFi. Lack or loss of response were the main reason for TNFi discontinuation, independently of TNFi position, responsible for more than half of the discontinuations. The observed short survival of TNFis in PsA, and the inability to regain drug expectancy when switching to another TNFi, highlights the limitations from recycling between TNFi when aiming at long-term disease remission. Acknowledgements: Financial support for statistics and report writing was provided by Novartis, Produtos Farmacêuticos S.A. Disclosure of Interest: None declared